2015
DOI: 10.3389/fimmu.2014.00680
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Programing by Endotoxin and Its Pathological Consequences

Abstract: Monocytes and macrophages play pivotal roles in inflammation and homeostasis. Recent studies suggest that dynamic programing of macrophages and monocytes may give rise to distinct “memory” states. Lipopolysaccharide (LPS), a classical pattern recognition molecule, dynamically programs innate immune responses. Emerging studies have revealed complex dynamics of cellular responses to LPS, with high doses causing acute, resolving inflammation, while lower doses are associated with low-grade and chronic non-resolvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
198
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(212 citation statements)
references
References 114 publications
(110 reference statements)
9
198
0
5
Order By: Relevance
“…In a time-dependent manner, VWR led to attenuations in the liver mRNA expression of known inflammatory markers (24). At 6 h post-LPS, there were attenuations in IL-6 and FST, while at 12 h post-LPS, IL-1␤ was attenuated, which together is indicative of a reduced inflammatory load.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In a time-dependent manner, VWR led to attenuations in the liver mRNA expression of known inflammatory markers (24). At 6 h post-LPS, there were attenuations in IL-6 and FST, while at 12 h post-LPS, IL-1␤ was attenuated, which together is indicative of a reduced inflammatory load.…”
Section: Discussionmentioning
confidence: 90%
“…Upon exposure to LPS, an inflammatory cascade is activated both systemically and at a tissue-specific level (1). Initial signaling involves a Toll-like receptor 4 (TLR4)-myeloid differentiation primary response gene 88 (MyD88) interaction that then propagates the inflammatory response (24). Increases in circulating inflammatory factors, such as TNF-␣, IL-6, and IL-1␤, occur rapidly and are regulated by the dose and duration of exposure (21,29,40).…”
mentioning
confidence: 99%
“…Recent efforts in the field of immunology provided evidence of adaptive characteristics of innate immunity, challenging the dogma that innate immunity is nonspecific. Morris et al (2014) suggested that TLR4 activation by very low doses of endotoxin may program host leukocytes into a low-grade "memory" state, contributing to the pathogenesis of chronic diseases. This is in contrast to findings described earlier in this review that endotoxin-induced activation of TLR4 prior to ischemic events has protective effects (Zacharowski et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It binds to LPS-binding protein (LBP) and the Toll-like-receptor (TLR) 4, which leads to the activation of the transcription factor NFκB through the MyD88 and interleukin-receptorassociated kinase (IRAK) signalling pathways [125]. NFκB acts as a spider in the web of inflammatory responses.…”
Section: Virulence Factorsmentioning
confidence: 99%